Answer:
1. reflection across x-axis
2. translation 6 units to the right and 3 units up (x+6,y+3)
Explanation:
The trapezoid ABCD has it vertices at points A(-5,2), B(-3,4), C(-2,4) and D(-1,2).
First transformation is the reflection across the x-axis with the rule
(x,y)→(x,-y)
so,
- A(-5,2)→A'(-5,-2)
- B(-3,4)→B'(-3,-4)
- C(-2,4)→C'(-2,-4)
- D(-1,2)→D'(-1,-2)
Second transformation is translation 6 units to the right and 3 units up with the rule
(x,y)→(x+6,y+3)
so,
- A'(-5,-2)→E(1,1)
- B'(-3,-4)→H(3,-1)
- C'(-2,-4)→G(4,-1)
- D'(-1,-2)→F(5,1)